2000
DOI: 10.1001/archfami.9.5.439
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Demographic Predictors of Late-Stage Cervical Cancer

Abstract: Women with cervical cancer who are elderly, unmarried, and uninsured are more likely to be diagnosed at a late stage. These women should be targeted for cervical cancer education and screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
1
11

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 43 publications
7
50
1
11
Order By: Relevance
“…Education has been linked to level of resources, cognition, and reception of health education messages (7,17); thus, the increased risk for advanced cancer of women with shorter education might be related to insufficient knowledge about cervical cancer and the prevention opportunities. Danish studies of cancers at other sites also found that shorter education was associated with more advanced cancer (20)(21)(22)(23), whereas studies of cervical cancer patients in New York City (n ¼ 2,930) and Florida (n ¼ 852) showed no association with education after adjustment for income and marital status (9,10). However descriptive statistics from the Florida study (9) and from a study in 5 U.S. states and 5 metropolitan areas (13) showed that women with short education were more likely to have regional spread cancer than women with higher education (37% vs. 51% and 31% vs. 38%, respectively).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Education has been linked to level of resources, cognition, and reception of health education messages (7,17); thus, the increased risk for advanced cancer of women with shorter education might be related to insufficient knowledge about cervical cancer and the prevention opportunities. Danish studies of cancers at other sites also found that shorter education was associated with more advanced cancer (20)(21)(22)(23), whereas studies of cervical cancer patients in New York City (n ¼ 2,930) and Florida (n ¼ 852) showed no association with education after adjustment for income and marital status (9,10). However descriptive statistics from the Florida study (9) and from a study in 5 U.S. states and 5 metropolitan areas (13) showed that women with short education were more likely to have regional spread cancer than women with higher education (37% vs. 51% and 31% vs. 38%, respectively).…”
Section: Discussionmentioning
confidence: 98%
“…Most of the previous studies of the effects of social factors on timing of cervical cancer diagnosis were conducted in the United States, used area-based measures of socioeconomic position, or focused on racial or ethnic differences (8)(9)(10)(11)(12)(13). We conducted a nationwide population-based study, with individual information on social indicators, to investigate the influence of socioeconomic position on stage at diagnosis of cervical cancer and, in addition, whether comorbidity and time since last Papanicolau (Pap) smear mediated this potential association.…”
Section: Introductionmentioning
confidence: 99%
“…30 There are other reports claiming that gynaecological cancers continue to represent a significant problem in the elderly. 22,31 As regards genitourinary tumours, the much poorer prognosis of older patients could be due to an inverse significant relationship of stage to age, and the complexity of surgical procedures as well as the particular physiological role of kidney. In addition, both bladder and kidney cancers have cigarette smoking as common etiologic factor and patients suffering from these tumours are often affected also by comorbid conditions, such as cardiovascular and pulmonary diseases which can mask the cancer symptoms and delay, or in someway vary, the time of diagnosis.…”
Section: Differences In Survival By Age: the Role Of Cancer Sitementioning
confidence: 99%
“…Incidence rates among these minority populations (2)(3)(4)(5)(6)(7)(8) and those who are uninsured (1,(9)(10)(11) have remained relatively stable for the past several years (12)(13), suggesting that system characteristics are likely preventing population health improvement.…”
Section: Introductionmentioning
confidence: 99%